Synthesis, characterization, and investigation of the thermal behavior of Cu(II) pyrazolyl complexes - da Silva, Patricia B. [UNESP]; Terra, Paulo H. [UNESP]; Frem, Regina Célia Galvão [UNESP]; Netto, Adelino Vieira de Godoy [UNESP]; Mauro, Antonio Eduardo [UNESP] (Springer, 2011)
This work reports the synthesis, characterization, and thermal behavior of three complexes of copper (II): [CuCl(2)(HPz)(4)] (1), [CuCl(2)(HdmPz)(4)] (2), and [CuCl(2)(HIPz)(4)] (3) (HPz = pyrazole; HdmPz = 3,5-dimethylpyrazole; HIPz = 4-iodopyrazole). The compounds were characterized by elemental analysis, infrared spectroscopy, and UV-Vis measurements. The thermal study of the compounds showed that the ligands are eliminated in 2-4 stages, yielding CuO as final residue.
Keywords: Cu (II) complexes; Pyrazolyl ligands; Thermal analysis